Publishables - Rebekka Kiesewetter (Diseña, 2020)
This article discusses academic (Open Access) publishing as a tool. On the one hand, with regards to a commercial publishing industry that ties in its inequalities in the institutional legitimation of knowledges with a neoliberal, competitive, and individualizing world view; as well as with regards to current models of policy and funding driven initiatives considering Open Access (OA) publishing as a business capitalizing on inequalities based on gender, class, and race embedded in systems of scholarly knowledge production. On the other hand, this article reviews current strands of scholar-led OA publishing initiatives that use publishing as a base for an interventionist practice geared at unsettling institutional and neoliberal frameworks of scholarly knowledge production and communication — conceptionally, formally, and organizationally. These initiatives are discussed within more speculative text sections unfolding around feminist and intersectional epistemologies, highlighting the performative, material, and relational character of publishing and publications. Thereby, this text aims to performatively point out possible different publishing formats, activities, and institutions, as well as different perspectives for and on publishing that might be instrumental for instantiating more horizontal and inclusive scholarly forms of knowledge production.